The Influence of Caregiving on Health-Related Quality of Life among American Indians - Spencer, S. Melinda (2013)
Caregiving can have a profound effect on the health of the caregiver, yet research on caregiving among American Indians is limited. The purpose of this study was to examine the influence of caregiving on health-related quality of life (HRQoL) among American Indians enrolled in the Education And Research Towards Health (EARTH) study. Participants in the EARTH study represented three different tribes in the Northern Plains and Southwestern regions of the U.S. who completed self-administered, computer-assisted questionnaires between 2003 and 2006. Participants were classified as either non-caregivers (n = 3,736) or caregivers if at least one adult relied on them for personal care. Caregivers were further classified by type; those caring for an adult with unspecified needs (CAU, n = 482), or those caring for an adult with mental and/or physical difficulties (CAD, n = 295). HRQoL was measured using the mental health and physical health component scores of the 12-Item Short-Form Health Survey. Regional differences emerged with regard to caregiver type. Across both regions, non-caregivers reported significantly better mental and physical health than CAD (p<0.01), and the health of participants classified as CAU did not differ from that of non-caregivers. The health of American Indian caregivers is dependent on the kind of care provided, but detailed measures of caregiving are necessary to understand how caregiving influences health. This has implications for the design of effective interventions in tribal communities.